Solitary Mastocytoma in Pediatrics. Case Report and Literature Review - Juan Carlos Yanes Macías; Mery Rosa Betancourt Trujillo; Lino Arístides Sánchez Galván (Revista Finlay)
The mastocytoma is a genodermatosis of unknown etiology, so it is included in the group of rare or uncommon diseases; it usually appears in childhood or at birth. It is characterized by local or systemic accumulation of primed cells, which causes the appearance of persistent, pigmented and very itchy skin lesions with exclusive skin involvement, usually presents as a single lesion in the neck, trunk, arms and legs. Typical features are that of a reddish-brown or yellowish brown nodule, of gummy consistency, the surface looks like orange peel, and Darier's sign. The case of a 4-month-old infant with a diagnosis of solitary mastocytoma with Darier's sign is presented. This report is made due to the low frequency of this disease at the Paquito González Cueto de Cienfuegos University Pediatric Hospital. Currently the patient is monitored by dermatology specialists, with antihistamine treatment and mast cell stabilizer.